System kar i nagród w szkołach ludowych w Galicji - Pelczar, Roman (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Celem artykułu jest zaprezentowanie sposobów karania i nagradzania uczniów w szkołach ludowych Galicji w całym okresie zaborów. Powstał on w oparciu o szeroką bazę informacyjną. Pozwoliło to bardzo szczegółowo przeanalizować szereg zagadnień związanych z tym tematem. Główną część artykułu stanowią treści poświęcone różnym rodzajom kar szkolnych, wśród których dominowały kary cielesne. Często stosowano także kary psychiczne. Znacznie rzadziej nauczyciele nagradzali uczniów. Artykuł uzupełnia wiedzę naukową na temat procesu dydaktyczno-wychowawczego realizowanego w szkołach w Galicji.

The aim of the article is to present ways of punishing and rewarding pupils in Galician folk schools throughout the period of partitions. It was based on a broad information base. This allowed a very detailed analysis of a number of issues related to this topic. The main part of the article is devoted to various types of school punishments, among which are corporal punishments. Psychic punishments were also frequently used. Much less often, teachers rewarded pupils. This article complements the scientific knowledge of the didactic and educational process used in schools in Galicia.
System of penalties and rewards in folk schools in Galicia
Keywords: szkoły ludowe w Galicji; kary szkolne; nagrody szkolne; nauczyciele szkół ludowych w Galicji; uczniowie szkół ludowych w Galicji; folk schools in Galicia; school sanctions; school awards; teachers of folk schools in Galicia; pupils of folk schools in Galicia